Cognitive and Emotional Dynamics in Identity Representation in Digital Discourse: A Psycholinguistic Analysis of Millennial Narratives on Social Media - Firdaus, Saiyidinal (SALEE: Study of Applied Linguistics and English Education, 2025)
This study consistently employs a qualitative narrative-psycholinguistic design to analyze the cognitive and emotional dynamics in the construction of millennial identity within digital narratives on X, Instagram, and TikTok. The analysis integrates thematic analysis, operationalized psycholinguistic coding based on Plutchik’s theory of emotions and Gee’s framework of identity representation, as well as a critical interpretive approach by Fairclough to situate the findings within the digital socio-cultural context. Data were collected through purposive sampling of at least 10 public narratives from each platform over a two-week period, using explicit criteria based on emotional intensity (marked by words, emojis, punctuation), and explicit/implicit identity representation. The findings indicate that X is dominated by collective reflection and resistance to stigma; Instagram foregrounds self-validation and authenticity; while TikTok displays humor-resilience as a coping strategy against socio-economic pressures. The analysis also reveals the prevalence of cognitive reflection patterns, emotional expression, and cross-platform identity synthesis, which aligns with recent studies on digital literacy and the psychological well-being of the millennial generation. The study’s contribution is to clarify the interrelationship between language, cognition, and emotion in shaping the digital identity of Indonesian millennials, as well as to underscore the importance of operational clarity and cross-platform synthesis in digital psycholinguistic research. The study recommends expanding research into cross-cultural contexts and over a longer duration to capture the dynamics of digital identity more comprehensively.